The Blackwell companion to maritime economics - Talley, Wayne Kenneth (Blackwell companions to contemporary economics, 2012)
The Blackwell Companion to Maritime Economics presents comprehensive and in-depth coverage of the entire scope of issues relating to shipping and port economics